White Pass Trail crossing in front of the Pack Train Saloon and the Clondyke Trading Co. with Skagaway Trading Co. and Bonanza Saloon in foreground, Skagway, Alaska, 1897 - Warner, Arthur Churchill, 1864-1943 (1897)
After gold was discovered in the Yukon Territory, thousands of people left for the Klondike to join in the gold rush in the Summer of 1897. The Pack Train Saloon in Skagway was owned by two individuals named Blaker and Hewitt and opened in August 1897. On verso of image: Skagway Warner [2000] Filed in Alaska series.